Pemblokiran PayPal sebagai Wujud Penyelenggara Sistem Elektronik Lintas Batas Negara - Bachry, Ramadhana Anindyajati; Sari, Noor Annisa Ditya (Faculty of Law, Universitas Jambi, 2023)
This article offers a solution to the blocking of PayPal involving international transactions across national borders in terms of the Minister of Communication and Informatics Regulation Number 5 of 2020 concerning Electronic System Operators (PSE). PayPal is a cross-border financial service provider application. The reason for the blocking is because PayPal did not register their permits, while socialization of the registration of the Electronic System Operator Program (PSE) policy has been given 2 (two) years. The PayPal application itself has provided massive financial services and one of the most users is in Indonesia. The use of PayPal by the global community is inseparable from its usefulness in facilitating cross-border transactions, in addition to waiving administrative fees for certain uses, PayPal is also considered to facilitate international transactions. Nonetheless, the blocking by the Ministry of Communication and Informatics poses difficulties for cross-border transactions. The difficulty consists in freezing accounts or foreign exchange owned by consumers. The brief reopening of the block resulted in consumers being materially harmed.Â This article uses normative law research methods.